Análise da paisagem na definição de áreas prioritárias para conservação e recuperação de remanescentes florestais de Juiz de Fora - MG - Rinco, Rosemay Martins (2009)
The present work makes a study in the district headquarters of the city of Juiz de Fora, Minas Gerais. It proposal a methodology that uses Geographic Information of System, ally to the studies of landscape ecology and observing the current law in moving to the units of conservation and the areas of permanent preservation. Criteria will be created to identify forest fragmenos with potentials of preservation as well as the possibility of connection of these, through of Area of Permanent Preservation, especificadamente, forest riparias, with or without vegetation. The generated material will be able to support the decision making process for investment of financial resources for compensation, as what it makes use the National System of Units of Conservation - Law 9.985/2000, aiming at sustainability of the landscape